FCJ-173 Being and Media: digital ontology after the event of the end of media - Justin Clemens; Adam Nash (Fibreculture Journal, 2015)
In the contemporary era, everything is digital and the digital is everything. Everything is digitized to data, then modulated between storage and display in an endless network of protocol-based negotiation that both severs any link to the data's semantic source and creates an ever-growing excess of data weirdly related to, but ontologically distinct from, its originating data source. Since the very ‘concept of medium' means that there are media, plural, i.e., differentiated media, and since the digital converges all media into a single state (that is to say, digital data), then by definition the concept of media disappears. Instead of media, there are simulations of media. This is the ‘event' that needs to be thought through. In this paper, we construct an ontology appropriate to the era of digital networks and draw out several consequences for the relationship between humans and digital networks.